Proton conducting polymer electrolytes based on PVDF-HFP and PVDF-HFP/PEMA Blend - Rudhziah .S; Muda .N; Ibrahim .S; Rahman .A.A; Mohamed .N.S (Universiti Kebangsaan Malaysia, 2011)
In the present work, polymer electrolytes of poly(vinylidene fluoride co-hexafluoroproplyne) (PVDF-HFP) and PVDF-HFP/poly(ethyl methacrylate) (PVDF-HFP/PEMA) blend complexed with different concentrations of ammonium triflate (NH4CF3SO3) were prepared and characterized. The structural and thermal properties of the electrolytes were studied by XRD and DSC while the electrical properties were investigated by impedance spectroscopy. Ionic transference number measurements were done by D.C polarization technique. The results of these study showed that the PVDF-HFP/PEMA based electrolytes exhibit higher ionic conductivity as compared to PVDF-HFP based electrolytes. This could be attributed to the higher degree of amorphicity in the PVDF-HFP/PEMA based electrolytes. The results of ionic transference number measurements showed that the charge transport in these electrolytes was mainly due to ions and only negligible contribution comes from electrons.